Teknik Yang Dapat Membantu Untuk Meningkatkan Keterampilan Berpikir Dan Daya Ingat Siswa - Salsa Riyanti; Rindang Putri (Jurnal Pengabdian Dian Mandala, 2023)
Creativity in students will be a guide for them when they face problems and make decisions in the future. Students are also able to receive feedback from experience or from teachers with the title of best student and teacher so that later they will be able and ready to receive the development of a creative mindset. A student feels useful and beneficial if he is involved in developing concepts to trigger his creativity and gain the ability to think with broad incentives (Anugraheni, 2018).